Materials for ultra-supercritical and advanced ultra-supercritical power plants - Di Gianfrancesco, Augusto (Elsevier Science, 2016)
Annotation Materials for Ultra-Supercritical and Advanced Ultra-Supercritical Power Plants provides researchers in academia and industry with an essential overview of the stronger high-temperature materials required for key process components, such as membrane wall tubes, high-pressure steam piping and headers, superheater tubes, forged rotors, cast components, and bolting and blading for steam turbines in USC power plants. Advanced materials for future advanced ultra-supercritical power plants, such as superalloys, new martensitic and austenitic steels, are also addressed. Chapters on international research directions complete the volume. The transition from conventional subcritical to supercritical thermal power plants greatly increased power generation efficiency. Now the introductions of the ultra-supercritical (USC) and, in the near future, advanced ultra-supercritical (A-USC) designs are further efforts to reduce fossil fuel consumption in power plants and the associated carbon dioxide emissions. The higher operating temperatures and pressures found in these new plant types, however, necessitate the use of advanced materials. Provides researchers in academia and industry with an authoritative and systematic overview of the stronger high-temperature materials required for both ultra-supercritical and advanced ultra-supercritical power plantsCovers materials for critical components in ultra-supercritical power plants, such as boilers, rotors, and turbine bladesAddresses advanced materials for future advanced ultra-supercritical power plants, such as superalloys, new martensitic and austenitic steelsIncludes chapters on technologies for welding technologies."
Keywords: Power-plants -- Materials.; elektronické knihy; electronic books